PKM Coping Stress Pada Mahasiswa - Muhammad Nur Hidayat Nurdin; Nurfitriany Fakhri (DEDIKASI, 2020)
This PKM activity aims to transfer of knowledge in the form of knowledge about stress, stress triggers, stress coping, types of coping, and steps of coping behavior. This activity was carried out in the campus hall involving 50 college students, namely STAI-DDI students, Tangnga Pangkep Regency. The methods used are brain storming, short film screening, material delivery by lecturing, discussion and sharing experiences. The result of this activity is the absorption of material about stress and stress coping by the participants (partners), which in turn can be used to deal with the stress they feel